Heavy Metal Contamination in Omo River, Ethiopia: Environmental and Human Health Risks - Kotacho Abiy Andemo; Yimer Girma Tilahun; Sota Solomon Sorsa; Berego Yohannes Seifu (SAGE Publishing, 2024)
The Omo River flows through the town of Omorate, where domestic, municipal, and industrial wastes from the town and its surroundings, including agrochemicals, are discharged into the river. The present study was conducted to determine the levels of heavy metals and associated environmental and human health impacts from the Lower Omo River freshwater ecosystem (water and sediment) of the Lower Omo River. The mean concentrations of heavy metals detected in the river water were 0.439 mg/l for (Mn), 0.1 (Zn), 0.168 (Cu), 0.393 (Cr), 0.318 (Pb), 0.007 (Ni), 8.926 (Fe), and 0.06 (Co).The order for the mean concentrations of the heavy metals in the water was Fe > Mn > Cr > Pb > Cu > Zn > Cu > Co > Ni. The HPI value indicates that all water sampling sites were highly contaminated. Oral and dermal HQs for both children and adults were in the order of Cr > Pb > Mn > Fe > Cu > Co > Ni > Zn. The HQ value greater than 1 was investigated for Cr, Pb, and Mn in both children and adults by ingestion and dermal routes from the river water. The CRs for both children and adults by ingestion of the river water followed the order Cr > Pb. According to the CRI value, the river water could be classified as a very high environmental risk. The EI results for the heavy metals detected in the sediments also followed the order: Fe > Cr > Cu > Pb > Mn > Co > Zn > Ni.